A Patent Data Analysis in Nanotechnology Applied to Essential Oils - Oliveira, Tainara S.; de Lima Silva, Vanessa; Assunção, Larissa Santos; de Jesus Freitas, Tayane; Machado, Bruna A. S.; Otero, Deborah Murowaniecki; Nunes, Itaciara Larroza; de Castro Almeida, Rogeria Comastri; Ribeiro, Camila Duarte Ferreira; Druzian, Janice Izabel (Recent Patents on Nanotechnology, 2022)
Background: Essential oils (EOs) are natural substances that serve as sources of bioactive compounds with antioxidant and antimicrobial properties. Objective: This objective is to understand intellectual property related to patent documents on EOs and nanotechnology. Methods: The nanotechnology growth curve applied to EOs demonstrated that the period from 2015 to 2017 was the most prominent, with a peak in 2016. China is the dominant country, mainly through research developed in the academic area. Results: The food industry area had the highest number of patents filed, highlighting the preservation line. Ginger essential oil, chitosan and Tween 80 were preferentially used as a core, wall material, and emulsifier, respectively. In the market, the use of EOs is more associated with the pharmaceutical/ cosmetics industry. In addition, the food industry market bets more on products based on hemp oil nanocapsules. Conclusion: EO nanotechnology is promising for the development of sustainable food systems. However, this nanotechnology in Brazil has not yet advanced enough in the food industry, although there are government incentives that may change this paradigm in the future. The profile of the patent documents and the products in the market differ between the application and the types of oils. In addition, there is a gap between the volume of patent documents investigated and the transfer of technology to the commercial sector, but this constitution could be better explored, given the properties of EOs.
Keywords: food preservation